Nationalism and immigration control. Issue 1 (10th November 2021) - Ko, Jiyoung; Choi, Seung‐Whan
Abstract: Does the rise of nationalism lead to immigration policy change? By focusing on elite‐led nationalism, this study offers a novel perspective: When top political leaders rely on nationalism as their legitimation strategy, they are more disposed to adopt policies aimed at strict immigration control, such as the imposition of sanctions on illegal immigrants, due to their hands being tied. We perform a battery of empirical tests using a cross‐national, time‐series data for 33 countries for the years 1980–2010. We find evidence that nationalist countries are positively associated with heightened immigration control. This finding is robust even after possible reverse causality is taken into account. The overall analysis illustrates that nationalism is a significant factor in explaining why countries are pushing for more restrictive immigration control in the contemporary world.